Integrating public engagement to promote transparent data use in a new UK-wide birth cohort - Raybould, Alyce; Dennison, Karen; McBride, Orla; Wong, Erica; Calderwood, Lisa; Fearon, Pasco; Goodman, Alissa (International Journal of Population Data Science, 2025)
Public engagement is an important mechanism for ensuring that the voices of the public are integrated into study design and data use. The commissioning of a new UK-wide birth cohort study by the UKRI Economic and Social Research Council (ESRC), the Early Life Cohort Feasibility Study (ELC-FS), necessitated renewed dialogue with the public about the acceptability of conducting a large-scale study of this kind. The ELC-FS recruited several thousand children in their first year of life, using an administrative data sampling frame, an `opt-out' recruitment approach, and embedded linkages to education, health and social care administrative data. The study faced many complexities and challenges to achieve this: the sampling frame had not been used for this purpose before, required negotiation with different data holders in the four UK nations, and the study needed to ensure transparency around how participants' administrative and survey data would be used. Conducting public engagement projects with parents of young children prior to the study's fieldwork was essential to understanding more about the public acceptability of data use in ELC-FS. Evidence from these projects was used to support negotiations with data holders, as well as in guiding best practice for informing participants about their data use and data linkage. This paper summarises the evidence from these public engagement projects relating to data transparency and enacting participant choice and control of the use of their data in the study. We describe how this evidence was implemented in three key study design areas: sampling and recruitment, the collection and use of survey data, and seeking participant consent to link administrative records to individual-level survey data. We also present evidence from the study's fieldwork about participants' acceptability of the survey design and transparency around data use, from recruitment to data collection and processing.